GAMBARAN HISTOLOGI USUS HALUS MENCIT (Mus musculus) JANTAN TIDAK BERHUBUNGAN DENGAN PERBEDAAN WAKTU FIKSASI MENGGUNAKAN LARUTAN NEUTRAL BUFFERED FORMALIN 10%: HISTOLOGICAL PICTURE OF THE SMALL INTESTINE OF MALE MICE (Mus musculus) IS NOT RELATED TO DIFFERENCES IN FIXATION TIME USING 10% NEUTRAL BUFFERED FORMALIN SOLUTION - Hasyimi, Ryadh Kamil; Hasanah, Nurul; Rahma, Khairunnida; Irawiraman, Hadi (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
Histotechnique is a technique to make specimens. These specimens can be used to analyze pathological conditions and changes in cells or tissues. Fixation is the most important factor that affects the histotechnique process. This study aim to determine whether there is a correlation between histological imagery of male mice (Mus musculus) intestine with different fixation times using Neutral Buffered Formalin 10% solution. The research was conducted using the true experimental method on 9 male adult Swiss Webster mice. The experimental design that used was 3 sample groups with 3 times replications. The used sampling technique was simple random sampling technique. The data on specimen quality obtained from the research were analyzed bivariately using the Kruskal-Wallis test. The group with the highest percentage of excellent specimen quality is the sample group fixated for 48 hours, with the percentage of 40%. The group with the highest percentage of poor specimen quality is the sample group fixed for 3 hours, with the percentage of 86.7%. The Kruskal-Wallis statistical test yielded a result of p = 0.217. Based on the findings, it can be inferred that there is no statistically significant correlation between histological characteristics of the small intestine of male mice (Mus musculus) intestine and variations in fixation duration when utilizing a 10% Neutral Buffered Formalin solution. Keywords: Fixation, Histotechnique, Intestine, Mice.